Effectiveness and impact of a single-dose vaccine against chickenpox in the community of Madrid between 2001 and 2015 - Pello Latasa; Angel Gil de Miguel; Maria Dolores Barranco Ordoñez; Inmaculada Rodero Garduño; Juan Carlos Sanz Moreno; María Ordobás Gavín; María Esteban Vasallo; Macarena Garrido-Estepa; Luis García-Comas (Taylor & Francis Group, 2018)
Background: Chickenpox is a contagious airborne disease. Immunization by varicella vaccine is an effective preventive measure. The objective of this study is to evaluate the impact and effectiveness of a single-dose vaccination against chickenpox at 15 months of age. Methods: Observational study based on data from the Epidemiological Surveillance System of the Autonomous Community of Madrid from 2001 to 2015. The years were grouped into 4 periods according to epidemic cycles and vaccination schedule: 2001-06, 2007-10, 2011-13 and 2014-15. The impact was calculated as Relative Risk (RR) between the incidence of chickenpox in children between 15 months and 13 years of age between 2011-13 and 2001-06 through Poisson regression using notifications made to the Diseases of Compulsory Declaration (DCD) system, the Sentinel Physicians Network (SPN) and hospital discharge records noted as Minimum Basic Data Set (MBDS). The vaccine effectiveness (VE) was calculated using the screening method and a 1:2 case-control study paired by age and paediatrician in population from 15 months to 13 years and between 2007 and 2015 using SPN source data. Results: The RR2011-13/2001-06 using data from the DCD was 0.14 (95% CI: 0.14 to 0.15), 0.07 (95% CI: 0.06 to 0.08) from SPN and 0.17 (95% CI: 0.15 to 0.20) from MBDS. A total of 338 cases were included in the VE screening obtaining an overall of 93.1 (90.9 to 94.8). For a case-control study, 120 cases and 247 controls were recruited obtaining a VE of 92.4% (IC 95%: 80.8 to 97.0%). Conclusions: The single-dose vaccination against chickenpox at 15 months of age has high impact and effectiveness.